Changing demographics, temporal trend in waitlist and post-transplant outcomes after heart transplantation in the United States: analysis of unos database 1991–2019. (14th October 2021) - Akintoye, E; Alvarez, P; Shin, D; Egbe, A; Panos, A; Briasoulis, A
Abstract: Background: The landscape of heart transplantation (HT) has changed significantly with respect to patient selection, surgical techniques, and patient outcomes. We sought to investigate temporal trends in patient characteristics, waitlist and post-transplant outcomes after HT in the U.S. Methods: We queried the national database of the United Network of Organ Sharing (UNOS) to identify adults listed for HT in the U.S. between 1991 and 2019. Patients were divided into four eras based on the three time points in which changes were made to the patient selection/allocation policy (1999, 2006, and 2018), and patient characteristics as well as waitlist and post-transplant outcomes were evaluated for each era. Results: Between 1991 and 2019, a total of 95, 179 patients were added to the waitlist for HT in the U.S. Compared to era 1, patients listed in era 4 were older (mean age: 52.4 years), more female (27.6%) and ethnic minorities (40%), and with higher-risk comorbidities (28.8% diabetes, 35.6% obese). Over the study period, there were 22, 070 waitlist deaths and 61, 687 transplants. Compared to the preceding era, there was significant decrease in waitlist mortality in the last 2 eras (e.g., sub-hazard ratio for era 4 vs era 3 =0.37, 95% CI=0.32–0.44). For each year, only 27.1% to 40.5% of those on the waitlist were transplanted. Among those who were transplanted, there was increase in the rates of in-hospital stroke (2.8% in era 1 to 3.7% in era 4), renal failure requiring dialysis (7.2% to 17.1%), and hospital length of stay (14 to 17 days), p-values<0.001 for all. However, this has not negatively impacted short-term survival when compared to the preceding era (1-year graft survival = 89.7% in era 4). Based on a projection model, we predict a 47% increase in living adult heart transplant recipients to to 44, 366 in 2040. Conclusion: There have been significant changes in the characteristics of patients listed for HT in the U.S., including an increasing proportion of high-risk co-morbidities. Although the transplant volume has increased, the wide supply-demand gap persisted. The last 2 changes in the allocation policy in 2006 and 2018 achieved their primary objective of reducing waitlist mortality. Funding Acknowledgement: Type of funding sources: None.